Activation Energy Effects on MHD Flow and Heat Transfer of a Carreau Nanofluid Past an Inclined Stretching Cylinder - Reddy, Kodandarami (Journal of Progress in Civil Engineering, 2026)
This study illustrates the effects of radiation, convective heating, activating energy, and second order velocity slip condition on the magnetohydrodynamic (MHD) Carreau nanofluid and heat/mass transfer. Brownian motion and thermophoresis effects are used in mathematical models of the Carreau nanofluid. A system of nonlinear coupled differential equations is created from the governing equations. The altered equations' solutions are obtained. Furthermore, a graphic representation of the effects of temperature, dimensionless velocity, and nanoparticle concentration profile is provided.